2013
DOI: 10.3389/fnint.2012.00128
|View full text |Cite
|
Sign up to set email alerts
|

What is social about social perception research?

Abstract: A growing consensus in social cognitive neuroscience holds that large portions of the primate visual brain are dedicated to the processing of social information, i.e., to those aspects of stimuli that are usually encountered in social interactions such as others' facial expressions, actions, and symbols. Yet, studies of social perception have mostly employed simple pictorial representations of conspecifics. These stimuli are social only in the restricted sense that they physically resemble objects with which t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 40 publications
1
20
0
Order By: Relevance
“…In this group, beliefs regarding social presence do not appear to affect gaze behaviour. One way of conceptualising the difference between the “recorded” and the “live” stimulus is that they are associated with different mental state inferences [Teufel et al, ]. In order for changes in gaze behaviour to occur, mental state inferences are made regarding the experimenter: for example, “she can see me” for the “live” stimulus, and these modulate behaviour in a top‐down manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this group, beliefs regarding social presence do not appear to affect gaze behaviour. One way of conceptualising the difference between the “recorded” and the “live” stimulus is that they are associated with different mental state inferences [Teufel et al, ]. In order for changes in gaze behaviour to occur, mental state inferences are made regarding the experimenter: for example, “she can see me” for the “live” stimulus, and these modulate behaviour in a top‐down manner.…”
Section: Discussionmentioning
confidence: 99%
“…However, they are necessarily limited in the extent to which the findings generalise to naturalistic settings. In recent years, there has been growing awareness of the need for a more ecologically valid approach to the study of social perception [Kingstone, ; Teufel et al, ]. In particular, the interactive aspects of social settings have been highlighted as a crucial but much neglected variable in social neuroscience [Schilbach et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…We thus created two conditions contrasted in terms of the associated belief to be watched by the other person or not, while maintaining identical low level visual properties of the stimuli. As mentioned above, previous studies have shown that the belief to be in live connection with another individual influences markedly the neural response to and the behavioural attention orienting effect of averted gaze (Teufel et al, 2013;Wiese et al, 2012). For this reason, we introduced a post-experiment debriefing interview, which allowed us to check if the participant had actually believed to be in online connection with another individual and to split the participants in two groups as a function of their belief in the deception procedure.…”
Section: Introductionmentioning
confidence: 99%
“…prolonged exposure to leftward gaze causes subjects to see subsequent gazes as shifted to the right). In contrast, they found that if the subject believes that the agent cannot see, adaptation to gaze direction either does not occur (Teufel et al, 2009) or is significantly attenuated (Teufel et al, 2013). 7 Other studies exhibiting similar effects include Nuku and Bekkering (2008) These findings strongly suggest that one's belief regarding whether another agent can see modulates the degree to which one attends to that agent's gaze.…”
Section: Is Gaze-following Automatic?mentioning
confidence: 92%
“…First, as explained above, there is converging evidence for a system dedicated to the perception of gaze direction. Moreover, the gaze-cueing effect appears to be modulated by adaptation to gaze direction (Bayliss et al, 2011;Teufel et al, 2009Teufel et al, , 2013. Second, not all asymmetries in low-level features trigger automatic shifts of attention.…”
Section: Is There a System Dedicated To Gaze-following?mentioning
confidence: 96%